Penguatan nilai tambah produk kopi Potokullin melalui proses produksi - A. Amanda Dhea Ayu Puspita; Heri Setiawan; Citra Ayunanda; Muhammad Iqbal Iskandar; Maryam; Achmad Rivaldy S; Al Imran; Andi Ahmad Zaeful; Walva Kano Pasaung; Jumriani Nasir; Andini Maharani B (Jurnal Dedikasi Masyarakat, 2022)
Potokullin Village in Enrekang Regency possesses the potential for a flagship product in the form of local coffee. However, the product’s added value has not been fully optimized due to the lack of exposure and optimization of its production process to consumers. This community service activity aimed to enhance the added value of Potokullin coffee by emphasizing each stage of the production process, from harvesting and processing to packaging. The methods used included participatory observation, documentation of each production phase, and analysis of their contribution to consumer perceptions of product quality. The results indicated that community involvement in the production process and hygienic processing serve as consumer appeal and strengthen the product’s image. The discussion emphasizes the importance of production process exposure as a means of educating consumers and branding local products.